2016
DOI: 10.1186/s40807-016-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving the carbon footprint of water treatment with renewable energy: a Western Australian case study

Abstract: A life cycle assessment (LCA) was carried out on three separate drinking water production options-a groundwater treatment plant (GWTP), surface water treatment plant and seawater desalination plant (electrodialysis) in order to calculate the carbon footprint associated with each process and to identify the areas of production with high levels of GHG emissions in order to develop strategies for reducing their carbon footprint. The results obtained from the LCA show that the highest GHG emissions are from the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Desalination plants accounting for Western Australia's largest water supply in the metropolitan area have been found to be a more carbon intensive water supply option compared to other existing options. For example, a local WA study found that to produce 1 GL of desalinated water, 3,890 tonnes of CO2 equivalent emissions would be evolved when grid electricity is the main source of energy, which is extremely high compared to other water supply options (Biswas and Yek 2016). This is also similar to a study in Denmark that found that groundwater was the least polluting in terms of greenhouse effect while desalination was the greatest polluting source (Godskeseen et al 2011).…”
Section: Introductionsupporting
confidence: 54%
“…Desalination plants accounting for Western Australia's largest water supply in the metropolitan area have been found to be a more carbon intensive water supply option compared to other existing options. For example, a local WA study found that to produce 1 GL of desalinated water, 3,890 tonnes of CO2 equivalent emissions would be evolved when grid electricity is the main source of energy, which is extremely high compared to other water supply options (Biswas and Yek 2016). This is also similar to a study in Denmark that found that groundwater was the least polluting in terms of greenhouse effect while desalination was the greatest polluting source (Godskeseen et al 2011).…”
Section: Introductionsupporting
confidence: 54%
“…The ve phases of the evaluated SWRO process are seawater pumping and intake, pretreatment, reverse osmosis operation, post treatment and water storage and distribution. Figure 3 shows the total carbon footprint of 3.5 × 10 −2 kg CO 2 -eq/year, with the assumption that the contribution was not signi cant and way smaller than the reported values of 1.599-5.63 kg CO 2 -eq for Spain, 2.208-7.46 kg CO 2 -eq for Israel, 2.562 kg CO 2 -eq for China, and 2.1-3.6 kg CO 2 -eq for Singapore (Pablo et al 2014;Jiahong Liu et al 2015;Biswas et al 2016;Xuexiu Jia et al 2019). The other contributing factors are plant capacity, adaptation of technology, fuel type, and the selection of attribute calculation in scopes 1, 2, and 3.…”
Section: C0 2-eq Emissions In the Operation Processmentioning
confidence: 78%
“…As mentioned earlier, SWRO sustainability is related to the alternative selection to minimise environmental impact, and the integration between the different sources of energy with a renewable energy was fundamentally selected to meet the objective. In other literature reviews, the energy reduction via membrane technology increases up to 38% with the integration of the hybridised SWRO and other renewable energies (Biswas et al 2016). The replacement of fossil fuel in a current desalination process is expected to reduce the cost of clean water production in Senak as well.…”
Section: Relationship Between Limitations Strategies and Adaptionmentioning
confidence: 99%
“…These two renewable energy resources along with the skilled workforce of WA could assist in the implementation of the renewable hydrogen projects in the state. Wind electricity is, however, more feasible in WA near the coastline area due to the availability of more wind resources [43,44]. Hydrogen plant location for the current study was also considered to be near the shoreline of the sea.…”
Section: Scenario Analysis Using Wind-energy-based Hydrogen Productionmentioning
confidence: 99%